Transdermal Pharmacokinetics Study of Extracts from Cortex Daphnes - Cheng1, Y.J.; Ma2, L.; Wei3, Z.P.; Yang4, C.H.; Han5, F.; Wang6, Y.F. (Asian Journal of Chemistry, 2013)
Extracts from Cortex Daphnes mainly contain daphnin, daphnetin-8-glucoside and daphnetin with a total proportion of 60 %. The main purpose of this study was to illustrate concentration profile of daphnin, daphnetin-8-glucoside and daphnetin in rabbit plasma after transdermal administration of extracts from Cortex Daphnes. A RP-HPLC method was used for simultaneous determination of the three components with a gradient solvent system. Ferulic acid was used as an internal standard. Sample preparations were carried out by extraction with ethyl acetate and deproteinization with methanol. The pharmacokinetic parameters were computed by software program DAS 2.1.1. Results indicated that blood pharmacokinetics of three compounds fit best to a two-compartment model. The maximum concentration (Cmax) varied due to different components, but the peak time (Tmax) of three compounds was about 0.75 h, indicating a fast absorption after administration.